2022
DOI: 10.1245/s10434-022-12595-w
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Universal Germline Genetic Testing for All New Breast Cancer Patients

Abstract: Background The American Society of Breast Surgeons recommends genetic testing (GT) for all women with breast cancer (BC), but implementation and uptake of GT has not been well-described. Methods A retrospective chart review was performed for newly diagnosed BC patients or patients with a newly identified recurrence of BC seen in a multidisciplinary clinic (MDBC) who were offered genetic counseling (GC) and GT. Results The 138 women attending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The rate of test uptake (192/210, > 90%) was similar to the 93% reported in a recent cohort of unselected BC patients seen at a comprehensive cancer center. 37 Of note, in that study, all patients met with a genetic counselor embedded in their multidisciplinary breast clinic, whereas in our study, pre-test education and the return of GGT results was performed by NGEs. A recent study of breast surgeons reported that those without in-house access to genetics services were more likely to use universal GGT.…”
Section: Discussionmentioning
confidence: 94%
“…The rate of test uptake (192/210, > 90%) was similar to the 93% reported in a recent cohort of unselected BC patients seen at a comprehensive cancer center. 37 Of note, in that study, all patients met with a genetic counselor embedded in their multidisciplinary breast clinic, whereas in our study, pre-test education and the return of GGT results was performed by NGEs. A recent study of breast surgeons reported that those without in-house access to genetics services were more likely to use universal GGT.…”
Section: Discussionmentioning
confidence: 94%
“…This proposition was also supported by the 2019 American Society of Breast Surgeons [25]. Owing to a high acceptance rate of genetic testing and counseling, more case detection would bene t treatment, screening, and prevention for patients and family members carrying pathogenic variants [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that lowering the age threshold for universal genetic testing could improve the detection rate in breast cancer patients 27 , which was supported by the 2019 American Society of Breast Surgeons 28 . Owing to the high acceptance of genetic testing and counseling, more detection of cases would benefit treatment, screening, and prevention for patients and family members carrying pathogenic variants 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%